Microstructure and physico-chemical bases of textural quality of yam products - AKISSOE, H. NOËL; Mestres, Christian; Handschin, Stephan; Gibert, Olivier; HOUNHOUIGAN, DJIDJOHO JOSEPH; Nago, Coffi Mathurnin (My University, 2011)
The texture of pounded yam is the main attribute of this traditional dish, one of the preferred ways of consuming yam in West Africa. We integrated functional properties and cell microstructure to describe or predict the textural quality of pounded yam. The firmness and adhesiveness of pounded yam prepared from six cultivars were measured. In parallel, the thermo-mechanical properties (DMA, DSC) and starch behaviour were also determined while the structure of raw, cooked and pounded yam was observed using Scanning Electron Microscopy, Light Microscopy and Confocal Laser Scanning Microscopy. No significant correlation was found linking DMA, DSC measurements with the textural quality of pounded yam (adhesiveness, firmness). Conversely, multiple regressions showed that 75% of the variation in firmness could be explained by the dry matter, soluble starch and amylose content of the pounded yam. In addition, CLSM revealed a thicker cell wall in Florido, a cultivar known for its bad pounding ability. We hypothesize that pectin, the major component of cell wall middle lamella, plays a role in the textural quality of pounded yam
Keywords: Pounded yam; Microstructure; Textural quality; Thermo-mechanical analysis; Starch solubility